Witchcraft and Biopsychosocial Causes of Mental Illness: Attitudes and Beliefs About Mental Illness Among Health Professionals in Five Countries. Issue 3 (March 2016) - Stefanovics, Elina A.; He, Hongbo; Cavalcanti, Maria; Neto, Helio; Ofori-Atta, Angelo; Leddy, Meaghan; Ighodaro, Adesuwa; Rosenheck, Robert
Abstract : Abstract: This study examines the intercorrelation of measures reflecting beliefs about and attitudes toward people with mental illness in a sample of health professionals ( N = 902) from five countries: Brazil, China, Ghana, Nigeria, and the United States, and, more specifically, the association of beliefs in supernatural as contrasted with biopsychosocial causes of mental illness. Factor analysis of a 43-item questionnaire identified four factors favoring a) socializing with people with mental illness; b) normalizing their roles in society; c) belief in supernatural causes of mental illness ( e.g., witchcraft, curses); and d) belief in biopsychosocial causes of mental illness. Unexpectedly, a hypothesized negative association between belief in supernatural and biopsychosocial causation of mental illness was not found. Belief in the biopsychosocial causation was weakly associated with less stigmatized attitudes towards socializing and normalized roles.